Ancient Egypt - Steele, Philip; Consultant Cobbling, Felicity (London Hermes House, 2007)
Step back in time to the world of the ancient Egyptians and discover the treasures and secrets of this mysterious 3,000-year-old civilization. Explore the culture and beliefs of the Egyptian people and enter an amazing world of gold-topped pyramids, mummified pharaohs, strange burial rituals and ingenious tomb robbers.
Include Color Illustration, Glossary and Index
Keywords: Civilization -- Antiquities -- Manners and customs